Inferential study on lifetime performance index with generalized inverted exponential model under progressive first-failure censoring (Statistics, Optimization & Information Computing, 2024)
Lifetime performance assessment is widely used in quality control of the manufacturing industry. This paper focuses on the progressively first-failure-censored data coming from the generalized inverted exponential distribution. We present the maximum likelihood estimate and the Bayesian estimate for the lifetime performance index (CL) for a given lower specification level L. The results are used to develop non-Bayesian and Bayesian inferences to determine whether the product performance meets the required level. A Monte Carlo simulation and two real data examples are discussed for illustration purposes.